IMPACT OF MOTHERHOOD ON WOMEN'S ACADEMIC CAREERS - Bandana Kumari (International Journal of Multidisciplinary Research and Studies, 2023)
During the 20th century, there was a significant rise in the number of women actively participating in the labour force, which resulted in one of the most revolutionary economic and social transformations of the century. The traditional roles of homemaker for men and breadwinner for women have become increasingly common in more developed countries. This increase in the number of women who are working was matched by a rise in the average level of education and credentials held by women. For instance, according to some recent statistics for the European Union, in 2016 around 44% of women (aged 30-34) had a postsecondary degree or above, whilst only 34% of males held that level of education (European Commission, 2017). The employment rates of women in the European Union are still lower than those of men; in 2016, the employment rate of 20-64 year old women in the EU was 65.3%, whereas the employment rate for men in the same age group was 76.8%. Although it is reasonable to assume that highly educated women are generally more likely to have some employment and pursue careers, the employment rates of women in the European Union are still lower than those of men (European commission, 2017). The employment rate of women was even lower than 60% in Greece, Italy, Malta, Croatia, Spain, and Romania. However, there are significant differences across nations, such as the fact that Greece, Italy, Malta, Croatia, Spain, and Romania. The degree to which women participate in the workforce is influenced by a wide variety of different circumstances.